Avaliação de parâmetros reológicos e imunológicos na infecção por Plasmodium vivax - Edson Fredulin Scherer (2015)
Malaria is a major infectious disease being considered reemerging in many countries and is caused by protozoa of the genus Plasmodium. Thus, the present study was to determine the serum concentration of cytokines and immunoglobulins - receptor expression for immunoglobulins in erythrocytes and rheological parameters in blood of people infected with P. vivax. We evaluated 69 subjects with 37 uninfected (control) and 32 infected with P. vivax from endemic areas in the states of Acre and Rondonia. The concentrations of IgA and IgG in the serum was performed by immunoturbidimetric method. The expression of receptors (CD16 +, CD32 +, CD89 +) in the membranes of erythrocytes and the concentrations of the INF- cytokines, TNF-, IL-2, IL-4, IL-6, IL-10 and IL-17 in serum citometriy assessed by flow. The concentration of TGF- was measured by ELISA. The rheological analyzes were performed in Modular Compact Rheometer and analyzed by Rheoplus software. It was observed that there was an increase of IgA in the serum of patients infected with P. vivax. The IgG concentration was not altered in the serum from these individuals. There was no change in the expression of the FcRI receptor (CD89 +) in erythrocytes of individuals infected with P. vivax. Expression of the CD32 + receptor was smaller while the increased expression of CD16 in individuals infected erythrocytes by P. vivax. The blood of infected individuals P. vivax has rheological change in viscosity. When used cytokines to enhance rheological parameters was observed that IL-17 decreased the viscosity of the blood of individuals infected with P. vivax, restoring blood viscosity values similar to those found in non-infected individuals. These data suggest that changes in the viscosity of blood may be relevant to help the clinical diagnosis of patients infected with P. vivax, and that IL-17 can be an alternate for future clinical applications immunomodulatory malaria.